Dimensi Metrik pada Graf Hasil Operasi Join pada Graf Lengkap dan Graf Tangga - Deddy Rahmadi; Awal Febriantono; Nurul Mufidah; Tsalis Wifqi Hidayati; Maulidatu Jauharoti Alisyah (UIN Walisongo Semarang, 2025)
The metric dimension of a graph is defined as the minimum cardinality of a resolving set of the graph. This study aims to determine the metric dimension of graphs obtained from the join operation between a complete graph and a ladder graph. The analysis begins by determining the metric dimensions of the constituent graphs, namely the complete graph K_n and the ladder graph L_m. Furthermore, the metric dimension of the graph resulting from the join operation K_n + L_m is investigated. The results show that the metric dimension of the complete graph K_n is n-1, the metric dimension of the ladder graph L_m is 2, and the metric dimension of the graph K_n+L_m is n+1.